An Artificial Olfactory Memory System for Monitoring and Recording of Volatile Organic Compounds. Issue 11 (2nd July 2021) - Ban, Chaoyi; Min, Xinjie; Xu, Jingxuan; Xiu, Fei; Nie, Yijie; Hu, Yuefan; Zhang, Heshan; Eginligil, Mustafa; Liu, Juqing; Zhang, Wei; Huang, Wei
Abstract: In biology, the sensory memory system plays a critical role by providing awareness and guidance for human action/decision. Olfactory memory, which is based on odor detection by receptor cells within the nasal cavity and followed by rapid decision making in the brain, is one of the most important, but least studied, sensory memory systems. Mimicking the olfactory memory by developing recognition, learning, and memorization of gas sensing is a long‐sought aim in artificial intelligence. Herein, an artificial olfactory memory system is experimentally demonstrated by integrating gas sensors with resistive memory. The system shows prominent selectivity toward volatile organic compounds (VOCs), and can be electrically programmed. The memory device can be triggered to sense gas above a certain threshold of VOC concentration, providing a smell sensation retaining, and leading to recognition of the gas information. This smart olfactory memory system can be directly used in robotics and artificial intelligent systems for various applications, such as environmental pollution control, early‐warning chemical and bio hazard safety, and augmented smart industrial production. Abstract : An artificial olfactory memory system is constructed to monitor and record volatile organic compounds by integrating gas sensors with resistive memory cells. The system provides an intelligent platform for selective, sensitive, and recognizable virtual nose‐to‐brain experience.